2007
DOI: 10.1007/s15010-007-7011-1
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Tuberculosis Following Total Knee Arthroplasty in an HIV Patient

Abstract: Skeletal tuberculosis is now uncommon in developed countries. In immunocompromised patients--particularly in the HIV-infected--who present with subacute or chronic joint pain refractory to conventional treatment, osteoarticular tuberculosis should still be included in the differential diagnosis. We report on a lethal case of disseminated tuberculosis in an HIV-infected subject. Dissemination may have resulted from the implantation of an articular prosthesis in a knee joint with unsuspected osteoarticular tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…3 Lack of clinical suspicion, inability to confirm the diagnosis even if clinically suspected, and coinfection with pyogenic bacteria from a chronically discharging sinus often lead to a delay in diagnosis. 11 Due to the rare nature of these infections and the lack of clear evidence, formulating treatment guidelines for these prosthetic joint infections are difficult. 2,9,10,12,13 The aim of this study was to report a rare presentation of lateonset of tubercular reactivation following TKA in a patient who was treated previously for latent tuberculous infection.…”
Section: Discussionmentioning
confidence: 99%
“…3 Lack of clinical suspicion, inability to confirm the diagnosis even if clinically suspected, and coinfection with pyogenic bacteria from a chronically discharging sinus often lead to a delay in diagnosis. 11 Due to the rare nature of these infections and the lack of clear evidence, formulating treatment guidelines for these prosthetic joint infections are difficult. 2,9,10,12,13 The aim of this study was to report a rare presentation of lateonset of tubercular reactivation following TKA in a patient who was treated previously for latent tuberculous infection.…”
Section: Discussionmentioning
confidence: 99%
“…The initial database queries produced 191 reports; 162 articles were excluded, including those that were duplicates (43), reviews or meta‐analyses (24), descriptions of general periprosthetic joint infections (25), descriptions of hip replacements (14), descriptions of non‐tuberculous mycobacterium infections (all case reports, 14), articles on knee joint tuberculosis replacements (23), and non‐English reports (19) 13–41 . We identified 44 cases of TBPJI described in the 29 selected articles.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, patients with TBPJI demonstrate weakened immune systems due to their being elderly, having autoimmune diseases (e.g. rheumatoid arthritis), using hormones, having undergone cancer chemotherapy, having AIDS, etc., making them susceptible to infection 26 . The average age of our four patients was 59.5 years, and the 44 patients with TBPJI reported in the literature had an average age of 70.14 years.…”
Section: Causes Of Missed or Misdiagnosed Joint Tuberculosismentioning
confidence: 99%
“…Patients with underlying causes of immunocompromise, history of tuberculosis infection, or patients with tuberculosis risk factors should consider the possibility of postoperative tuberculosis infection prophylaxis [13]. Marschall et al [21] reported about a 48-year-old male patient with a history of HIV and CD4+ count of 7/uL, who presented with painless swelling of the joint six months after TKA. He was diagnosed with TBPJI at nine months and passed away one month after diagnosis.…”
Section: Reviewmentioning
confidence: 99%